2017
DOI: 10.1002/adem.201700357
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Study of Deformation Twinning and Detwinning in Helium Irradiated Small‐Volume Copper

Abstract: The influence of nanoscale helium bubbles on the deformation twinning and detwinning behavior of submicron‐sized Cu is investigated under tension, compression, and cyclic loading. In situ nanomechanical tests performed inside a transmission electron microscope reveal that twinning and detwinning occur readily in helium irradiated copper under both tension and compression. Continuous shearing of helium bubbles by Shockley partials leads to twin formation, whereas the residual back‐stress accumulated from disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Hence, nano/micro-mechanical tests are widely adopted to evaluate He bubble induced hardening in these sample. Nanoindentation [63,116,117], and in situ mechanical testing in SEM [118,119,120,121] and TEM [122,123,124,125,126,127] are widely performed to investigate the effect of He bubbles on the mechanical properties of various metals. We mainly focus on three parts next: He irradiation hardening in single-phase metals, He irradiation hardening in metallic multilayers and theoretical modeling of He irradiation hardening.…”
Section: Helium Radiation Hardeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, nano/micro-mechanical tests are widely adopted to evaluate He bubble induced hardening in these sample. Nanoindentation [63,116,117], and in situ mechanical testing in SEM [118,119,120,121] and TEM [122,123,124,125,126,127] are widely performed to investigate the effect of He bubbles on the mechanical properties of various metals. We mainly focus on three parts next: He irradiation hardening in single-phase metals, He irradiation hardening in metallic multilayers and theoretical modeling of He irradiation hardening.…”
Section: Helium Radiation Hardeningmentioning
confidence: 99%
“…We start the discussion with He irradiation hardening in single-phase metals. Several studies are performed on He irradiated steel [63], Ni [120], Cu [118,122,123,124,125,126] and Al–4Cu alloy [127] to evaluate He radiation hardening and interactions of He bubble with dislocations/deformation twin [63,120,121,122,123,124,125,126,127]. Using nanoindentation teats, Roldan et al [63] found that He-irradiated steels after annealing demonstrate much higher hardness compared with as-received samples.…”
Section: Helium Radiation Hardeningmentioning
confidence: 99%
“…23 Within the past decade, development of depth-sensing transmission electron microscopic (TEM) in situ mechanical testing holders 10 has further enhanced our ability to resolve and quantitatively understand nanomechanical phenomena. TEM in situ mechanical testing has been conducted in compression, 24 tension, 19,24 bending, 25 and indentation 26 modes to investigate a wide range of nanomechanical behaviors at the atomic through nano-scale, including dislocation slip, [27][28][29] twinning, 30,31 diffusionless phase transformations, 32 bubble shearing, 30,33 and irradiation effects. 26,34,35 Advancements in computation since the late 1990s have developed in concert with the aforementioned experimental methods.…”
mentioning
confidence: 99%
“…Hence, nano/micro-mechanical tests are widely adopted to evaluate He bubble induced hardening in these sample. Nanoindentation [63,116,117], and in situ mechanical testing in SEM [118][119][120][121] and TEM [122][123][124][125][126][127] are widely performed to investigate the effect of He bubbles on the mechanical properties of various metals. We mainly focus on three parts next: He irradiation hardening in single-phase metals, He irradiation hardening in metallic multilayers and theoretical modeling of He irradiation hardening.…”
Section: Helium Radiation Hardeningmentioning
confidence: 99%
“…We start the discussion with He irradiation hardening in single-phase metals. Several studies are performed on He irradiated steel [63], Ni [120], Cu [118,[122][123][124][125][126] and Al-4Cu alloy [127] to evaluate He radiation hardening and interactions of He bubble with dislocations/deformation twin [63,[120][121][122][123][124][125][126][127]. Using nanoindentation teats, Roldan et al [63] found that He-irradiated steels after annealing demonstrate much higher hardness compared with as-received samples.…”
Section: Helium Radiation Hardening In Single-phase Metalsmentioning
confidence: 99%